A new beta titanium alloy system reinforced with superlattice intermetallic precipitates. (November 2017) - Knowles, Alexander J; Jun, Tea-Sung; Bhowmik, Ayan; Jones, Nicholas G; Britton, T Ben; Giuliani, Finn; Stone, Howard J; Dye, David
Abstract: Titanium alloys traditionally lack a nm-scale intermetallic precipitate that can be exploited for age-hardening from solid solution. Here such a strengthening concept is developed in the Ti-Fe-Mo system, with it being found that a high temperature β (bcc A2) single-phase field for homogenisation can be obtained, which following ageing (750 °C/80 h) precipitated B2 TiFe <100 nm in size. The orientation relationship was found to be ⟨100⟩A2 //⟨100⟩B2, 100A2 //100B2, with a misfit of −6.1%. The alloy was found to be very hard (HV0.5 = 6.4 GPa) and strong ( σ y, 0.2 = 1.9 GPa) with a density of 6.68 g cm −3 . TEM observation and micropillar deformation showed that the precipitates resist dislocation cutting. Graphical Abstract: Aged hardened beta titanium alloy reinforced with superlattice TiFe precipitates (a) microstructure by BSE SEM, (b) matrix-precipitate orientation relationship in a TEM SADP, (c) micropillar stress strain curve ( σ 0.2 = 2.8 GPa) and (d) post-deformation micropillar after 10% strain.